2016
DOI: 10.1039/c5ra26695e
|View full text |Cite
|
Sign up to set email alerts
|

Selective separation and identification of metabolite groups of Polygonum cuspidatum extract in rat plasma using dispersion solid-phase extraction by magnetic molecularly imprinted polymers coupled with LC/Q-TOF-MS

Abstract: In this work, magnetic molecularly imprinted polymers (MMIPs) were successfully prepared for specific recognition and selective enrichment of metabolite groups of Polygonum cuspidatum extract in rat plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…M4 and M13 all showed m / z 307 [M‐H] − , which produced the main fragment ions at m / z 227 in their MS E spectra, indicating the presence of a sulfate. Therefore, compounds M4 and M13 were characterized as resveratrol‐ O ‐sulfate, according to reference . M7, M8, and M9 were detected [M‐H] − at m / z 485, and fragment ions were detected at m / z 309, 229, and 187, suggesting the addition of two hydrogen atoms compared with those in the structure of M3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M4 and M13 all showed m / z 307 [M‐H] − , which produced the main fragment ions at m / z 227 in their MS E spectra, indicating the presence of a sulfate. Therefore, compounds M4 and M13 were characterized as resveratrol‐ O ‐sulfate, according to reference . M7, M8, and M9 were detected [M‐H] − at m / z 485, and fragment ions were detected at m / z 309, 229, and 187, suggesting the addition of two hydrogen atoms compared with those in the structure of M3.…”
Section: Resultsmentioning
confidence: 99%
“…Fragment ions at m / z 269, 241, and 225 were diagnosed ions of emodin, and the fragment ions at m / z 445 and 269 were formed by successive losses of sulfate (80 Da) and glucuronic acid (176 Da) from the [M‐H] − . Therefore, M11 was interpreted to be emodin‐ O ‐glucuronide sulfate, according to the literature . M16 produced [M‐H] − at m / z 461 and fragment ions at m / z 285, 268, 257, 255, 241, 227, and 211.…”
Section: Resultsmentioning
confidence: 99%
“…But, to achieve a complete elimination of MEs, a selective extraction should be planned and performed [19,20]. Recently, the development of molecular imprinted technology (MIP) should provide the analyst with new opportunities in terms of selective extraction, high recovery percentage and low MEs [21,22], but unfortunately this technology is not yet commercially available. Generally, the more similar the polarity between the target analytes and the matrix composition, the less chance there is for efficient and selective extraction step using the common extraction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…So comprehensive study of biotransformation pathways and the knowledge of the possible toxicity of metabolites are prerequisite for the drug discovery and development . Over the years, liquid chromatography–electrospray ionization tandem mass spectrometry (LC–ESI/MS/MS) in combination with accurate mass measurements has been widely used for the identification and characterization of metabolites …”
Section: Introductionmentioning
confidence: 99%
“…[10] Over the years, liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI/MS/MS) in combination with accurate mass measurements has been widely used for the identification and characterization of metabolites. [11][12][13][14] Comprehensive literature search revealed that there are several analytical and bioanalytical reports on chromatographic determination of FLU, [15] such as UV determination, [16] kinetic studies on FLU photo degradation, [17] chiral evaluation by HPLC-ESI/MS, [18] determination of FLU and other drugs used in cardiovascular therapy by liquid chromatography-mass spectrometry (LC-MS/MS), [19] fluorometric determination of its enantiomers, [20] effects of clopidogrel [21] and fluconazole [22] on its pharmacokinetics, UV determination of simvastatin and FLU in serum and formulation, [23] HPLC method for determination of FLU and its metabolites in plasma, [24] and quantification of FLU by LC-MS/MS. [25] A few metabolites of FLU have been reported [26] by using HPLC coupled with the radioactive monitoring with a run time of 120 min.…”
Section: Introductionmentioning
confidence: 99%